An evaluation of University of Cape Town medical students' community placements in South Africa - Claudia S. Naidu; Virginia Zweigenthal; James Irlam; Leslie London; Johannah Keikelame (AOSIS, 2012)
Background: Fourth-year medical students at the University of Cape Town (UCT) work closely with stakeholders in community teaching sites to conduct community-based research projects and follow-up health promotion interventions during their Public Health training.Objectives: This study evaluated the placements as a learning experience from the perspectives of past students and community stakeholders.Methods: A total of 32 projects were randomly selected out of 232 projects undertaken during 2006, 2008 and 2009. Two students and a stakeholder involved with each project were sampled. A standardised survey was emailed to students and in-depth interviews were held with stakeholders.Results: Fifty two per cent of 64 students and 57% of 25 stakeholders responded. Most students felt that the placements enhanced their academic experience and confidence in research skills, and were an effective form of learning. Perceived challenges included time constraints and, for a minority, inadequately prepared settings and stakeholders. Stakeholders felt that the placements empowered the communities and prepared students for the realities of working as a medical professional. They viewed students as a valuable resource and believed that student projects addressed important community myths and health problems. Recommendations from students and stakeholders included more time for the Public Health block, followup interventions for greater continuity, and better alignment of projects with stakeholder programmes.Conclusion: The evaluation reveals both the importance and challenges of community placements and identifies areas of improvement. Despite the limited duration of the placements, they offered valuable community-based learning experiences for the students and worthwhile benefits for the communities.